2017
DOI: 10.1161/jaha.117.005869
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Integrity and Function in the Progression of Early Pressure Overload–Induced Left Ventricular Remodeling

Abstract: BackgroundFollowing pressure overload, compensatory concentric left ventricular remodeling (CR) variably transitions to eccentric remodeling (ER) and systolic dysfunction. Mechanisms responsible for this transition are incompletely understood. Here we leverage phenotypic variability in pressure overload–induced cardiac remodeling to test the hypothesis that altered mitochondrial homeostasis and calcium handling occur early in the transition from CR to ER, before overt systolic dysfunction.Methods and ResultsSp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…A rate of protein synthesis that is higher than the degradation rate while the level of NSPs is declining suggests an imbalance of mitochondrial homeostasis, with many dysfunctional proteins as well as impaired oxidative capacity in the face of high energy. These data fall in line with observations in HF patients and post-infarct mice with cardiac remodeling (Murphy, Ardehali et al 2016, Chaanine, Sreekumaran Nair et al 2017). Mitochondrial proteins may have a higher synthesis than degradation rate in MCR (scenario 2 in Table 1 ); however, both the synthesis and degradation rates are most likely much lower compared to the sham group, clarifying the lower levels of NSPs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A rate of protein synthesis that is higher than the degradation rate while the level of NSPs is declining suggests an imbalance of mitochondrial homeostasis, with many dysfunctional proteins as well as impaired oxidative capacity in the face of high energy. These data fall in line with observations in HF patients and post-infarct mice with cardiac remodeling (Murphy, Ardehali et al 2016, Chaanine, Sreekumaran Nair et al 2017). Mitochondrial proteins may have a higher synthesis than degradation rate in MCR (scenario 2 in Table 1 ); however, both the synthesis and degradation rates are most likely much lower compared to the sham group, clarifying the lower levels of NSPs.…”
Section: Discussionsupporting
confidence: 92%
“…Our data also reveal that the majority (50%) of the protein dynamics detected is relevant to the biological processes of oxidative phosphorylation and mitochondrial function (Figures 4A and 4B); these proteins exhibited decreased levels of NSPs in parallel to a rate of protein synthesis greater than that of protein degradation (increased protein turnover rate, scenario 2 in Table 1 ). Perturbations in mitochondrial homeostasis and metabolism are essential mechanisms in the pathophysiology of cardiac remodeling and HF (Chaanine, Sreekumaran Nair et al 2017). Previous observations suggest that mitochondrial biogenesis, signaling, and oxidative capacity are preserved or increased in the early stages of cardiac remodeling in order to match the energy demand imposed by a detrimental stressor such as ISO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence was recently reported that endothelial Tspan5- and Tspan17-ADAM10 complexes contribute to inflammation by maintaining VE-cadherin expression and promoting T lymphocyte transmigration ( 78 ). Another injury-related gene that was upregulated was BNIP3 , which is associated with mitochondrial autophagy and apoptosis and is increased in the heart by pressure overload and various stresses ( 79 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased mitochondria content is also in line with the severe myocardial fibrosis observed in these mice. In this context, it is noteworthy that the development of DCM with eccentric remodeling after left ventricular overload has been shown to result in enhanced mitochondrial apoptosis and impaired mitochondrial function which, however, only took place after a post-intervention period of eight weeks in healthy rats [33]. Moreover, decreases in respiratory chain function after pressure overload to the heart only take place with the beginning of impaired left ventricular function [34].…”
Section: Plos Onementioning
confidence: 99%